Physical and chemical changes of seven selected herbs used as herbal bath affected by different drying methods - Md Zuki, Rose Fazila; Ismail, Mohd Firdaus; Aziz, Julia Abdul (Universiti Putra Malaysia, 2024)
The effect of oven drying (OD) at 50±5°C, sun drying (SD), and fresh leaves (control) of seven selected herbs used in herbal preparation as herbal baths were evaluated. Herbal baths (HB) involve mixing herbs into water and boiling them or simply immersing them in the mixture during a regular bath. The herbs selected were leaves of torch ginger, greater galangal, pandan, citronella grass, henna, betel leaves, and kaffir lime leaves and fruits. The herbs were planted in a plot at the Institute of Bioscience, Universiti Putra Malaysia, Malaysia. Physical changes such as HB herbs’ colour, aroma, and chemical composition were evaluated. The hydro distillation method was used for the extraction process of HB herbs, where it produced essential oils (EO), essential water (EW), and boiling water (BW), and their chemical composition was determined by gas chromatography-mass spectrometry. As a result, the OD herbs possessed brighter and more attractive colours compared to the SD method, which was dull and pale. The colour of EO was yellow, colourless for EW, and reddish for BW. Additionally, OD herbs possessed 80% and only 50% of the scent strength of the SD herbs from extracting fresh herbs. The fresh and dried HB herbs contained chemical constituents mostly from the terpene group. Herbal preparation developed using all treatments retained an appreciable amount of chemical composition studied, thus having the potential for commercial purposes. ©